Social transformation in Bangladesh : pathways, challenges and the way forward - Rahman, Shahidur; Masud-All-Kamal, Md. (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This book examines the underlying causes of Bangladesh's success story since its independence; a country that has been praised for its economic development and commendable achievements on human development indices. It offers a critical analysis of the social transformation that has taken place. Chapters in this edited book offer interdisciplinary perspectives analyses concerning issues of inclusivity, extractivism, sustainability and equitability. The book takes a look into the interconnected metamorphosis of the economy, society, culture, and environment of Bangladesh. From the products of post-industrial society such as YouTube sensations and digital labour platforms, to groups that have gone through marginalisation for decades such as the urban poor, and indigenous peoples, a wide array of scholarship and case studies are utilised to analyses the challenges and opportunities offered by the process of societal transformation. This book will be of great interest for those specialising in the fields of South Asian Studies, Development Studies, Sociology, Migration, Labour, Health and Media Studies"--
Includes bibliographical references and index.
Hye Trade International
Keywords: Bangladesh -- Social conditions; Bangladesh -- Economic conditions